Development of Ecotourism in Svalbard as Part of Norway’s Arctic Policy - Grzegorz Bonusiak (Sustainability, 2021)
Global warming is increasing interest in the Arctic on surrounding countries. In the processes taking place, they see developmental opportunities and risks, especially for the environment overburdened by increased human activity. The need to balance socioeconomic development and environmental concerns affects their arctic strategies. An example of a place that undergoes an adaptation process is the Norwegian Svalbard. The article examines changes taking place in the archipelago using both: quantitative and qualitative analyses. Results show that Norway’s arctic strategy underlines the need to balance social, economic and environmental aspects, and the situation in Svalbard corresponds to these demands. Polar tourism and research and education play a key role in the transformation processes taking place in the archipelago. Climate and environmental considerations at the same time increase tourists’ interest in the region and limit tourist traffic. An analysis of its current state indicates that the dominant part of the existing tourist traffic on Svalbard can be considered as ecotourism.